Advanced landfill liner systems - August, H.; Holzlohner, U.; Meggyes, T. (Thomas Telford, 1997)
This work summarises the results of 27 research projects carried out within a DM15 million integrated research programme in Germany. The results show that the mechanical properties of earthen and cut-off materials can be improved and that testing methods and apparatus are available for the determination of critical values.